Application of Real Option Approach in China Real Estate Development-A case study - Chen, Lu (2007)
The real estate development in emerging economies such as in China presents great uncertainty due to unstable macroeconomic conditions and regulatory changes over the life of the investment project. The traditional valuation approach Discount Cash Flow (DCF) model may be insufficient to evaluate real estate project since it cannot properly deal with the uncertainty, irreversibility and managerial flexibility of the real estate investment and thus lead to inadequate decision has been made. Instead, this paper will use a real option approach which remedies these shortfalls and provides a more scientific valuation for a real estate investment project.